Ayyām-e Fāṭimiyya as an Alternative ʿĀshūrāʾ: The Mourning of Fāṭima in Modern Iran - Zeynep Sena Kaynamazoğlu (İslam Tetkikleri Dergisi)
The mourning ceremonies performed in the month of Muḥarram constitute the most important element of Shīʿite public religiosity. The memory ofthe Karbalāʾ incident and the martyrdom of al-Ḥusayn b. ʿAlī is immortalized, and the Shīʿite consciousness is transmitted across generations due to ‘Āshūrā’ ceremonies, which have developed over the centuries by adding new elements to their structure. This mourning, which has deeply affected the Shīʿite tradition, has transcended its borders in time and created a culture of mourning unique to the Shīʿite tradition. Seemingly, mourning was limited to the commemoration of the martyrdom of ʿAlī b. Abī Ṭālib and his son al-Ḥusayn b. ʿAlī until the Qajar period. However, within this period, the religious calendar was colored, and new days and nights were included in the Shīʿite public religiosity. Moreover, the importance attached to these special religious occasions has increased due to the Iranian Revolution. One of the most remarkable phenomena that has found a place in the Shīʿite popular piety in the modern period is the mourning ceremonies that commemorate the death and martyrdom of the daughter of Prophet Muḥammad named Fāṭima al-Zahrāʾ (d. 11/632). These mourning ceremonies, which are held on days called ayyām-e fāṭimiyya, are the most important religious commemoration after Muḥarram ceremonies in modern Iran. On these days, cortege-style marches are held on the streets in many provinces of Iran, rawḍakhānī assemblies are organized in homes and mosques, and cultural programs and stands that introduce Fāṭima al Zahrāʾ are organized in schools and official institutions. This study mainly examines the formation of the ayyām-e fāṭimiyya and its performance, religious background, and related controversies. In this context, the article draws attention to debates that focus on the narrations that Fāṭima al-Zahrāʾ was subjected to violence and died as a result. It also aims to discuss the importance of Fāṭima al-Zahrāʾ for modern Iranian women and the influence of Muḥarram ceremonies on Shīʿite popular piety and other ceremonies.